056 Variability in adult epilepsy prevalence in the UK. Issue 3 (9th February 2012) - Thomas, R H; Steer, S; Gilpin, T R; Glasbey, J C D; King, W H; Smith, P E M
Abstract : Describing the 'burden of disease' is essential when designing health services. The prevalence of epilepsy is currently thought to be 490 000 (children and adults in the UK) but the Joint Epilepsy Council believes that 590 000 people carry the diagnosis. It is not known whether there are important inequalities in prevalence; nor whether specialist centres are in the areas of greatest need. The quality and outcomes framework (QOF) is an 'annual reward and incentive programme for all GP surgeries…detailing practice achievement results'. Since the inception of QOF (2004), GPs are required to create a register of all their patients (over 18) with an epilepsy diagnosis, who are currently on one or more anti-epileptic drugs. We collated the number of people with epilepsy per PCT/LHB present maps of both crude prevalence and those standardised for poverty; corrected using indices of multiple deprivation. Data were available for 100% of practices. 408 775 adults carry an epilepsy diagnosis in the UK: (Scotland 39 695 (0.73%); Wales 22 885 (0.73%); England 332 001 (0.61%); Northern Ireland 14 194 (0.76%)). Prevalence was lowest in affluent Chelsea & Kensington (0.34%) and highest in impoverished former mining communities in Wales: Rhondda Cynon Taf and Neath Port Talbot (0.84%). This is the first community survey of adult epilepsy prevalence to use this method. Our maps demonstrate variability in epilepsy prevalence; apparently higher in urban areas, areas of social deprivation and areas without a specialist service. Identifying and removing inequalities in service provision and health outcome is an essential part of ensuring best possible care for everyone with epilepsy.